2006
DOI: 10.1210/jc.2005-1076
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Serum-Soluble Vascular Endothelial Growth Factor Receptor-1 in Early Pregnancy Ending in Preeclampsia or Intrauterine Growth Retardation

Abstract: Elevated sVEGFR-1 concentrations at 16-20 wk gestation precede the clinical manifestations of preeclampsia. By neutralizing VEGF, sVEGFR-1 may contribute to inadequate placental vascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
74
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 26 publications
7
74
2
1
Order By: Relevance
“…In contrast with our results, they had made their study on 1000 women, 500 cases and 500 controls [14].…”
Section: Discussioncontrasting
confidence: 85%
“…In contrast with our results, they had made their study on 1000 women, 500 cases and 500 controls [14].…”
Section: Discussioncontrasting
confidence: 85%
“…Our findings are similar to those reported by Wathen et al, who observed a fall of 15% in the serum concentration of sFlt1 from 14 to 19 weeks during normal pregnancy in contrast to increased levels of sFlt1 from 16 to 20 weeks in women with subsequent preeclampsia. 18 Of further interest is the similarity of the measurements from the CPEP trial performed more than 12 years ago and the present MOMS protocol, supporting the use of these assays in samples appropriately stored over long periods of time.…”
Section: Discussionmentioning
confidence: 53%
“…The contribution of sVEGFR-1 to the maternal syndrome of preeclampsia is thought to be, at least in part, related to its inhibition of VEGF stimulation of the endothelium-dependent nitric oxide system (through VEGFR-2) [86]. Plasma sVEGFR-1 concentration has been found to be elevated in preeclampsia both prior to [87][88][89][90][91][92][93][94] and after clinical diagnosis [84,87,[95][96][97][98][99]. In contrast, studies of plasma sVEGFR-1 concentration in women with SGA fetuses have yielded conflicting results-either no change [100] or an increase [99].…”
Section: Introductionmentioning
confidence: 99%